Human insulin specific suppressor factors. I. Induction, characteristics and comparison to murine factors. - Kontiainen, S (1982)
Suppressor factors were produced from normal human peripheral blood mononuclear cells by culturing them in vitro with high doses of monocomponent pork or beef insulin. These factors were tested in vitro on mouse spleen cells, using cooperative cultures of pork insulin induced helper cells of BALB/c origin and normal BALB/c spleen B cells stimulated by DNP-pork insulin. The insulin suppressor factors abolishing pork insulin specific helper cell activity were, like other human antigen specific suppressor factors described, antigen specific, carried Ia-like (DR) determinants and the factor 'constant' region markers. Insulin suppressor factors, however, lacked analogue specificity i.e. pork insulin specific helper activity could be abolished by both pork and beef insulin induced suppressor factors. All individuals tested so far were able to produce equally efficient suppressor factor to pork and beef insulin. This is unlike insulin antibody production. The possibility that insulin antibody production and insulin suppression were under different genetic control and the possible explanations for the lack of analogue specificity are discussed.